Ketersediaan Vegetasi Pada Koridor Jalan Ngesrep Banyumanik - Poppy Poppy; Hadi Wahyono (Jurusan Perencanaan Wilayah dan Kota, 2016)
Reduced land area of green open space for the availability of the vegetation along the corridor street Ngesrep be reduced aesthetic value of the corridor. Availability of vegetation plays an important role in the effective functioning of green open space which serves as the aesthetic value is also beneficial to absorb air pollution. Lack of availability of vegetation on Ngesrep corridor street associated with the lack of proportion of areas allocated for open space and cause a decrease in the level of welfare. Directly causes decreased aesthetic value of green environment and the means to participate groundwater reserves decline. This study aims to identify the availability of vegetation on street corridor Ngesrep in fulfillment of a shortage of green space in the street corridor. Using descriptive quantitative research methods and analysis used is descriptive quantitative analysis to describe the results of the acquisition of the questionnaire and descriptive qualitative analysis to explain and generalize the results of penilitian form of interviews.Based on the results of the study the condition of vegetation found along the street corridor Ngesrep very concern and bad, which can no longer function ecologically to the surrounding environment. Total availability of vegetation such as trees without any other plants very little variation, as many as 143 trees for a length of 1.5 km on the right side and the left shoulder of the road. Low levels of government in the care and cultivation of new crops. Almost 90% of the vegetation conditions including bad categories and should be the turn of the new plant. Proposals for improving the availability of vegetation on street corridor Ngesrep need for rules and sanctions for those individuals who perform the cutting of trees and the hardening of the shoulder of the road without permission. Thus the availability of vegetation on the green line on the road corridors Ngesrep not just be a complementary element in spatial planning of road corridors, rather it is one of the spatial structure of the road corridor.